Pengaruh Bahan Ajar Berbasis Potensi Lokal terhadap Kemampuan Berpikir Kritis dan Sikap Peduli Lingkungan Siswa - Maulida Rahmi; Siti Nurhidayati; Taufik Samsuri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study aims to determine students' critical thinking skills and environmental care attitudes through teaching materials based on local potential. This research was conducted at SMA Negeri 2 Labuapi for the 2021/2022 academic year. This type of research is a quasi-experimental with a population of all 111 class X students divided into 5 classes. The sampling technique used by researchers in this study was a purposive sampling technique by taking class X MIPA 1 as the experimental class, and class X MIPA 2 as the control class. Design research with a pre-test post-test control group design. The data collection techniques used were observation techniques, direct communication techniques, documentary study techniques and indirect communication techniques, namely, using essay tests for critical thinking skills and using questionnaires for environmental care attitudes. The data analysis technique used is descriptive analysis. the results of the study show that there are differences in critical thinking skills and environmental care attitudes between the experimental class that uses teaching materials based on local potential, compared to the control class that uses TCL or conventional learning models. The results of this study were taken from the results of the final ability (post-test) of students from both classes, namely the experimental class, which scored higher than the control class, which indicates that teaching materials based on local potential affect critical thinking skills and environmental care attitudes of SMA Negeri 2 Labuapi students. This can be seen from the value of the t-test results of the critical thinking ability score, namely 9.708 and the t-test of the results of the environmental care attitude value, namely 7.124 and the ttable value is 2.3226. Then tcount > ttable which means that H0 is rejected and H1 is accepted. it can be concluded that teaching materials based on local potential affect the ability to think critically and care for the environment of students.